By 2079, aridification will have reduced the GDPs of Africa and Asia by 16% and 6.3%, respectively - Maurizio Malpede; Marco Percoco (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2021)
We examine the effects of human-induced desertification on economic growth by exploiting a 56 km-by-56 km grid-cell global dataset on the annual frequency from 1990-2015. We find that areas that experienced large soil aridification are associated with a reduction in GDP per capita. Our results indicate that from 1990-2015, aridification reduced the GDPs of African and Asian countries by 12% and 2.7%, respectively. Our estimates are robust to adding higher-order terms of geo-climatic variables and controlling for country-specific linear trends, which allows us to project future costs of desertification. Our findings show that desertification will generate losses in GDP growth by 16% and 6.7% in Africa and Asia, respectively.
Keywords: 330